Decision to Delivery Interval, Fetal Outcomes and Its Factors Among Emergency Caesarean Section Deliveries at South Gondar Zone Hospitals, Northwest Ethiopia: Retrospective Cross-Sectional Study, 2020 - Degu Ayele A; Getnet Kassa B; Nibret Mihretie G; Yenealem Beyene F (Dove Medical Press, 2021)
Alemu Degu Ayele,1 Bekalu Getnet Kassa,1 Gedefaye Nibret Mihretie,1 Fentahun Yenealem Beyene2 1Department of Midwifery, College of Health Sciences, Debre Tabor University, Debre Tabor, Ethiopia; 2Department of Midwifery, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, EthiopiaCorrespondence: Alemu Degu AyeleDepartment of Midwifery, College of Health Sciences, Debre Tabor University, PO Box 272, Debre Tabor, EthiopiaTel +251920770887Email degualemu53@gmail.comPurpose: Although its fetal outcomes and practicality are unclear time interval between decision-to-delivery ≤ 30 minutes in emergency caesarean section (CS) is the internationally accepted standard of practice. This study aimed to determine whether a decision to delivery interval (DDI) of approximately 30 minutes was achieved in daily practice, its fetal outcomes, and associated factors among emergency caesarean section delivery at South Gondar Zone Hospitals, Northwest Ethiopia.Patients and Methods: Retrospective cross-sectional study was carried out from August 1– 30/2020 among emergency caesarean sections. Information was collected from the birth register book and individual files of standardized facility booking forms. The data was encoded and entered into Epi-Data version 4.2 and exported to SPSS version 23 for analysis. A bivariable and multivariable logistic regression analysis was conducted and a significant association was recorded at p< 0.05.Results: Only 17.5% of parturients attained a decision-to-delivery interval ≤ 30 minutes. The average median of decision to delivery interval was 54 minutes with interquartile range (IQR) of 48– 80 minutes. Time taken to collect material with Adjusted odds ratio (AOR=10.3, 95% CI 5.87– 45.7), time of decision (AOR=0.32, 95% CI, 0.15– 0.67), and time taken from decision to delivery to delivery of anesthesia (AOR=4.74, 95% CI, 1.30– 17.3) were the predictors of prolonged delivery time interval. Significant fetal adverse outcomes were not observed in a decision to delivery interval higher than 30 minutes.Conclusion: In most cases, delivery was not completed within the prescribed ≤ 30-minutes interval, particularly in developing countries with infrastructural challenges, however, fetal outcomes were not directly correlated. Despite lack of substantial linkage between the delivery time declaration and fetal events, an unreasonable gap from the decision-making to birth of the child is not appropriate and should be discouraged.Keywords: caesarean section, decision to delivery interval, fetal outcome, Ethiopia